Description of Patient Safety Culture Based on AHRQ Method in Employees of St.Madyang Hospital, Palopo City - Rahayu, Sri Hastari; Harma, Asmarani (Universitas Wiralodra, 2025)
Patient safety is a primary concern as it has now emerged as an international challenge confronting the healthcare system in hospitals. Patient safety is intimately tied to the incidence of Patient Safety Incidents within hospitals. The initial step in a hospital's patient safety initiative is to cultivate a culture of patient safety or to enhance awareness among all staff regarding the significance of safety values in hospitals. This research was conducted to evaluate the patient safety culture of all employees at St. Madyang Hospital, Palopo City in 2024. The measurement in this study that based on AHRQ (2019) version 2.0 method from the side of hospital staff can be measured through 10 dimensions, where categories of patient safety culture are grouped into three categories consisting of weak culture, medium culture, and strong culture. The results of the study showed a positive response of 68% or included in the category of Medium Safety Culture. The highest patient safety culture, which is 91%, is achieved in the Communication About Errors dimension. While the lowest cultural achievement is in the Number of Error Reports dimension, which is 33%. It is essential to motivation employees regarding the reporting of incidents in the hospital, as consistent reporting can subsequently facilitate easy access and safety in reporting, aimed at promoting safety and guaranteeing that health services will avert accidents or injuries in the future.